Pharmacokinetics, in vitro and in vivo correlation, and efficacy of exenatide microspheres in diabetic rats. (January 2015) - Li, Xingang; Zhao, Zhigang; Li, Liang; Zhou, Tianyan; Lu, Wei
Abstract Modeling and simulation are aimed at achieving information about the behaviors of the drugs without the actual measurements and determination. The purpose of this study was to characterize the in vivo behavior of exenatide microspheres using model-based methods. Exenatide is a glucagon-like peptide-1 agonist medication, belonging to the group of incretin mimetics, approved for the treatment of diabetes mellitus type 2. An oil-in-water solvent evaporation method was used to prepare the exenatide microspheres and their physicochemical features were investigated. After subcutaneous injection of exenatide microspheres to streptozotocin-induced diabetic rats, the exenatide concentrations increased and kept increasing and the blood glucose decreased in all diabetic rats. The in vivo release behavior of exenatide from microspheres was described by a transit compartment model. Based on the transit compartment model, the simulation method was proposed for the description of in vivo release. The in vitro and in vivo correlation (IVIVC) was established by the model-based simulation (R2 = 0.903) and deconvolution (R2 = 0.922) methods successfully. Using a transit compartment model to characterize the in vivo exenatide release from microspheres is an acceptable approach, and the IVIVC can be estimated reliably with the model-based simulation method.